Energy System Performance Investigation of Serneke Arena - Larsson, Sara; Ottosson, Frida (My University, 2023)
Serneke Arena wanted to investigate methods to make the energy systems at the arena more effective. The arena has a high energy demand today where the indoor skiing facility Skidome responds to 33.8 % and 1.54 GWh of the total electricity use. The largest focus on energy efficiency measures was therefore on Skidome in this project. With only three ski arenas built in Sweden, and a few more in the planning phase, the knowledge regarding optimal operation of indoor cross-country ski facilities are limited today. With little literature and few experts within the area this thesis was made to get a deeper understanding of how the indoor ski facility of Skidome in Göteborg could be more energy efficient. The main task with the thesis was to create a deeper understanding about the system and how it is operated today and suggest improvements. The system has few sensors installed and the possibilities to get historical data and trends from the energy system was limited. Therefore, one part in the project was to identify temperatures and moisture levels in the ventilation air to Skidome, as well as flows and temperatures of the cooling process. This was made through several different measurements in the system with different methods. Further five investigations were made to analyse how different actions would affect the energy performance of Serneke arena. The results shows that there are possible ways to make the energy system more efficient compared to how it operates today. The coefficient of performance of the cooling machines was investigated and could be optimized for the cooling process and save up to 11.5% of the cooling machines total energy demand if the condensing temperature was reduced. The air handling unit operating in Skidome was investigated to determine how it performs today. There are optimization possibilities in terms of how it is operated in different outdoor conditions, to both reach a better temperature and dehumidification operation. The heat in the indirect warm stream in the condensing processes in the cooling machine is utilized 32% for heat recovery to heat pumps and 68% is cooled off in dry coolers. There are possibilities to save money by locally produce hot tap water instead of buying from the district heating net. The investigation to utilize existing boreholes for comfort cooling resulted in saving 2.2% of the total electricity use in Serneke arena.
Keywords: Indoor cross-country skiing, energy efficiency, energy performance, energy system improvements, cooling systems, artificial snow